Evaluation of the efficiency of interspecies embryo transfer between alpacas and llamas obtained through single ovulation - Pacheco, Joel (2016)
This study aimed to evaluate the efficiency of embryo recovery in single ovulation, the quality of the embryos and the interspecies fertility through embryo transfer. Nine donor alpacas and 40 recipient llamas were used. Ultrasonography of the ovaries was done to determine the presence of an ovulatory follicle. Donors were naturally mated and washing of uterine horns was performed at 7 days post-breeding. After collecting the embryos, cloprostenol was injected to donors to induce luteolisis and reinitiate a new follicular wave. Four washes were performed with intervals of 15 days. The transfer of fresh embryos was done on day 7 (group 1) or 6 (group 2) after the induction of ovulation with buserelin to the recipients. The results showed that 58.3% of embryos were collected. Among them, 57.2, 23.8 and 19.0% were of grade 1, 2 and 3 respectively. None embryos were of grade 4. Fertility on day 21 after the transfer of embryos was 33.3 and 11.1% for groups 1 and 2 respectively (mean: 20%), without recording embryo mortality in controls at 90 and 150 days post-transfer.